THE APPLICATION OF SPEED READING TECHNIQUE IN READING ACTIVITY FOR STUDENTS OF SENIOR HIGH SCHOOL 1 KLUET SELATAN - Suhailida; Surya Asra; Rollis Juliansyah (Journal of Education, Linguistics, Literature and Language Teaching, 2021)
The study aims to observe the application of speed-reading techniques to improve reading skills for students in SMAN 1 Kluet Selatan. The research took place through Classroom Action Research (CAR) in class XII-IPA 1, which consisted of 27 students and involved a researcher (as a teacher) and an observer. The results of this study indicate that the use of speed reading techniques can improve students' reading skills. The technique application is confirmed to be effective if supported by the teacher's ability to plan the lesson in the classroom. It includes proportional activities in the teaching and learning process and a conducive classroom atmosphere created by providing learning facilities and infrastructure. The success of applying the speed reading technique is confirmed by the appearance of positive student responses and their active participation in each learning activity. Keywords: speed reading technique, reading activity, reading ability